Marine Exopolysaccharide Complexed With Scandium Aimed as Theranostic Agents - Mattia Mazza; Cyrille Alliot; Corinne Sinquin; Sylvia Colliec-Jouault; Pascal E. Reiller; Sandrine Huclier-Markai (Molecules, 2021)
(1) Background: Exopolysaccharide (EPS) derivatives, produced by Alteromonas infernus bacterium, showed anti-metastatic properties. They may represent a new class of ligands to be combined with theranostic radionuclides, such as 47Sc/44Sc. The goal of this work was to investigate the feasibility of such coupling. (2) Methods: EPSs, as well as heparin used as a drug reference, were characterized in terms of molar mass and dispersity using Asymmetrical Flow Field-Flow Fractionation coupled to Multi-Angle Light Scattering (AF4-MALS). The intrinsic viscosity of EPSs at different ionic strengths were measured in order to establish the conformation. To determine the stability constants of Sc with EPS and heparin, a Free-ion selective radiotracer extraction (FISRE) method has been used. (3) Results: AF4-MALS showed that radical depolymerization produces monodisperse EPSs, suitable for therapeutic use. EPS conformation exhibited a lower hydrodynamic volume for the highest ionic strengths. The resulting random-coiled conformation could affect the complexation with metal for high concentration. The LogK of Sc-EPS complexes have been determined and showing that they are comparable to the Sc-Hep. (4) Conclusions: EPSs are very promising to be coupled with the theranostic pair of scandium for Nuclear Medicine.